Development and Pilot Testing of a Dispensing Protocol on Emergency Contraceptive Pills for Community Pharmacists in Belgium - Michael Ceulemans; Marieke Brughmans; Laura-Lien Poortmans; Ellen Spreuwers; Julie Willekens; Nele Roose; Isabelle De Wulf; Veerle Foulon (MDPI AG, 2022)
Community pharmacists in Belgium frequently dispense emergency contraceptive pills (ECPs). However, variable and insufficient counseling practices exist across pharmacies, highlighting the need for standardization and quality improvement strategies. The aim of this project was to develop and test an ECP dispensing protocol for pharmacists. An 'experience-based' co-design approach involving academic and practicing pharmacists was applied, followed by a 4-month test period and interviews to assess users' experiences. In total, eight geographically dispersed pharmacies participated. Pharmacists (n = 15) reached a consensus on most items to be included in the protocol, which was subsequently tested in seven pharmacies, with overall 97 registered ECP conversations. Pharmacists considered the protocol complete but felt that not all items should be mentioned/questioned during all conversations. They suggested only subtle modifications to be made prior to delivering a final protocol ready for nationwide distribution. Despite attributing positive effects to having a protocol, no single pharmacist 'actively' used it at-the-counter but used it instead as a 'checklist' after the encounter. Pharmacists found that the paper-based format of the protocol hindered protocol-based dispensing. Future research is needed to provide evidence on the actual benefits of protocol application, as well as to identify factors influencing the implementation of ECP dispensing using a software-integrated protocol.